2015
DOI: 10.1055/s-0034-1392417
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Barrett’s esophagus with a novel focal cryoablation device: a safety and feasibility study

Abstract: Background and aims: Currently, eradication of Barrett?s epithelium is preferably achieved using radiofrequency ablation (RFA) or spray cryoablation (SCA). However, both modalities suffer from drawbacks such as the need for sizing, multiple deployment steps, large controller units (RFA), imprecise dosing and need for gas-venting (SCA). The new Cryoballoon Focal Ablation System (CbFAS) may address these limitations. This study assessed the safety, feasibility, and dose response of the CbFAS in patients with fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…1E and G). All patients underwent at least 1 cryoablation procedure (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The total number of cryoablation procedures for the intention-to-treat cohort was 117, with a technical success rate of 115 of 117 (98%) because of 2 incomplete cryoablation treatments (2 patients) related to balloon migration from a pre-existing stricture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1E and G). All patients underwent at least 1 cryoablation procedure (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The total number of cryoablation procedures for the intention-to-treat cohort was 117, with a technical success rate of 115 of 117 (98%) because of 2 incomplete cryoablation treatments (2 patients) related to balloon migration from a pre-existing stricture.…”
Section: Resultsmentioning
confidence: 99%
“…A prior human dosing trial demonstrated 100% ablation of IM in a focal area treated with 10 seconds of cryogen. 12 Similarly, a recent 30 patient clinical trial showed that 10 seconds of ice applied with the focal cryoballoon device was successful in targeting dysplastic BE islands in 94% and associated with 100% CE of BE treated. 13 Procedure times for cryoballoon ablation are short, averaging 30 minutes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A newer device is also available to deliver cryotherapy using nitrous oxide via a self-contained, balloon based system [127]. Cryoablation can achieve complete eradication of HGD in a high proportion of patients with BE in retrospective studies, with good durability during a 24-month follow-up period [128, 129].…”
Section: Managementmentioning
confidence: 99%